2016
DOI: 10.1038/ncomms11941
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous incorporation of gold in palladium-based ternary nanoparticles makes durable electrocatalysts for oxygen reduction reaction

Abstract: Replacing platinum by a less precious metal such as palladium, is highly desirable for lowering the cost of fuel-cell electrocatalysts. However, the instability of palladium in the harsh environment of fuel-cell cathodes renders its commercial future bleak. Here we show that by incorporating trace amounts of gold in palladium-based ternary (Pd6CoCu) nanocatalysts, the durability of the catalysts improves markedly. Using aberration-corrected analytical transmission electron microscopy in conjunction with synchr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 39 publications
3
57
0
Order By: Relevance
“…On the other hand, for the Pt 2 M alloy system, Pt 2 Mo has been identified as the best candidate with a low ORR kinetic barrier . Besides Pt 2 M and Pt 3 M, the ORR properties of Pt‐lanthanides, Pt‐alkali earth elements, and Pt 5 M alloys have also been comprehensively investigated . It was found that these Pt‐based catalysts exhibited excellent activities that were three to six times better than Pt.…”
Section: Primary Non‐li Metal–o2 Batteries With Aqueous Electrolytesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, for the Pt 2 M alloy system, Pt 2 Mo has been identified as the best candidate with a low ORR kinetic barrier . Besides Pt 2 M and Pt 3 M, the ORR properties of Pt‐lanthanides, Pt‐alkali earth elements, and Pt 5 M alloys have also been comprehensively investigated . It was found that these Pt‐based catalysts exhibited excellent activities that were three to six times better than Pt.…”
Section: Primary Non‐li Metal–o2 Batteries With Aqueous Electrolytesmentioning
confidence: 99%
“…Plenty of binary, ternary, and some multiple‐element Pd alloys have been discovered and presented much improved catalytic performances, such as Pd 11 Fe, Pd 11 Co, PdCo, Pd 3 Fe, Pd 3 Pb, Pd 2 NiAg, Pt–Pd–Au, etc . The improved catalytic performance of Pd alloys can be attributed to the compression of PdPd bond aroused by the addition of secondary transition metals, which lead to the downshift of d‐band center to improve the ORR performance . Multiple‐element alloys have much more complicated structures and catalytic mechanisms but also are an effective way to enhance both the catalytic activity and stability.…”
Section: Primary Non‐li Metal–o2 Batteries With Aqueous Electrolytesmentioning
confidence: 99%
“…The diffusion coefficient (D S ) of atoms and temperature can be related as follows: D S ∝ exp − E ai kT , where E ai is the activation energy, K is the Boltzmann constant, and T is the annealing temperature. In response to sufficient diffusion, voids/pinholes can be perforated at the low energy sites in the thin films: i.e., at misfit dislocations, triple junctions, grain boundaries, and steps on substrates [18]. Then, along with the temperature increment, the diffusion and inter-mixing of atoms can be enhanced through the pinholes.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the localized surface plasmon resonance (LSPR) frequency of alloy NPs can be modulated through the composition variation, which potentially enables many applications in the plasmonic, energy, and biomedical fields. For instance, the durability of Pd-based nanocatalysts has been significantly improved by the addition of Au in the NPs [18] and the incorporation of Pd into Ag NPs can demonstrate a red shift of plasmon resonance peak from 440 to 732 nm along with the increased Pd composition [19]. In recent years, monometallic Au, Ag, and Pd NPs have been successfully utilized in many fields Figure 1 shows a general depiction of AuPdAg alloy NPs fabrication on sapphire (0001) based on the temperature control along with the different evolution stages.…”
Section: Introductionmentioning
confidence: 99%
“…The results from the structural and electrochemical characterizations suggested different correlations between the catalytic activity, atomic-scale structure and composition of the materials, bearing in mind the changes presented for Pd 50 Cu 50 /C after the durability potential cycling. Other work reported the preparation of ternary catalyst with Pd, Cu and Co, increasing their activity and durability with the incorporation of gold traces [75] this noble metal galvanically replaced Co and Cu and entered into the Pd-Co-Cu lattice. The catalyst with the major durability (close to 100 h) was the Au-Pd 6 CoCu/C, according with the results displayed by the single fuel-cell test, a result attributed to the homogeneous distribution of gold into the nanoparticles and the enhanced charge transfer between Pd and Au.…”
Section: Carbon-supported Pd-alloysmentioning
confidence: 99%